Protective Effect of Rosmarinus officinalis L. Essential Oil against Free Radical-Induced Erythrocyte Lysis: Cytoprotective effect of Rosmarinus officinalis - Karimi, Gholamreza; Hassanzadeh, Mohammad; Mehri, Soghra (Iranian Journal of Pharmaceutical Sciences, 2005)
The oxidative hemolysis of rat erythrocytes induced by 2,2’-azobis–(2-amidinopropane) (AAPH) and its inhibition by rosemary essential oil was studied. Different concentrations (0.178, 0.357, 0.534 and 0.712 μl/ml) of the essential oil showed no significant hemolysis compared to phosphate buffer solution. AAPH (25 mM and 50 mM) induced hemolysis in a time-dependent manner. Diff e r e n t concentrations of the essential oil inhibited hemolysis induced by 25 mM AAPH. However, in the presence of 50 mM of AAPH, only the two higher concentrations (0.534 and 0.712 μl/ml) of the essential oil inhibited hemolysis. Addition of essential oil 2 or 3 h after incubation with AAPH had no significant effects on the time course of cell lysis. It is concluded that, in addition to its well-established antioxidant effects, rosemary essential oil displays cytoprotective properties.